Autoimmune Polyendocrinopathy-Candidiasis-Ectodermal Dystrophy - Ferré, Elise M. N.; Schmitt, Monica M.; Lionakis, Michail S. (Frontiers in Pediatrics, 2021)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED), also known as autoimmune polyglandular syndrome type-1 (APS-1), is a rare monogenic autoimmune disease caused by loss-of-function mutations in the autoimmune regulator (AIRE) gene. AIRE deficiency impairs immune tolerance in the thymus and results in the peripheral escape of self-reactive T lymphocytes and the generation of several cytokine- and tissue antigen-targeted autoantibodies. APECED features a classic triad of characteristic clinical manifestations consisting of chronic mucocutaneous candidiasis (CMC), hypoparathyroidism, and primary adrenal insufficiency (Addison’s disease). In addition, APECED patients develop several non-endocrine autoimmune manifestations with variable frequencies, whose recognition by pediatricians should facilitate an earlier diagnosis and allow for the prompt implementation of targeted screening, preventive, and therapeutic strategies. This review summarizes our current understanding of the genetic, immunological, clinical, diagnostic, and treatment features of APECED.